Peningkatan Kemampuan Evaluasi Guru Melalui Supervisi Klinis di SDN 156/X Tanjung Solok Tahun Ajaran 2021/2022 - Asniwati Asniwati (Journal on Education, 2022)
This study aims to obtain data/information and discuss the improvement of teacher evaluation skills through clinical supervision of supervisors at SDN 156/X Tanjung Solok. This research is school action research (PTS) which consists of two cycles by following four stages of planning, implementation, observation, and reflection. This research was conducted at SDN 156/X Tanjung Solok in the odd semester of the 2021/2022 academic year with 6 teachers as the subject. Data were collected through observation sheets and documentation and analyzed using percentages and data reduction. The results of the study show that clinical supervision can improve teacher evaluation abilities.